Clinical and chest CT manifestations of Talaromycosis marneffei: a retrospective study comparing anti-IFN-γ autoantibodies-positive and HIV-positive cases - Xiuting Wu; Yuhui Zhong; Zefeng Li; Chunchen Wei; Yumin Lu; Kai Li (BMC Infectious Diseases)
Abstract Background To explore the clinical and chest CT features of Talaromycosis marneffei (TSM), and to compare the differences between anti‑IFN‑γ autoantibodies‑positive and HIV-positive cases. Methods Clinical data and chest CT images of 54 HIV-negative patients with Talaromyces marneffei (TM) infection and positive anti-interferon-γ (anti-IFN-γ) autoantibody were retrospectively analyzed. Ninety-three HIV-positive patients with TM infection during the same period were included as controls. Differences between groups were compared by the two-sample t-test and the Mann-Whitney U test, respectively. Results The time from symptom onset to diagnosis of TSM with positive anti-IFN-γ autoantibodies was significantly longer than that of controls (P < 0.001). BALF/sputum and lymph nodes were the better specimens for detecting TM in the anti-IFN-γ autoantibody-positive group, while TM were more often isolated or detected in blood samples in the other group. Patients with TM infection tended to present with cough, expectoration, and fever. Compared with controls, anti-IFN-γ antibody-positive patients with TM infection had a higher incidence of shortness of breath, skin lesions, joint pain, and high CD4/CD8 ratio (P < 0.05). There were only 1 and 6 cases with negative lung involvements in CT scans in anti-IFN-γ autoantibody-positive patients and HIV-positive patients with TM infection, respectively. In the remaining patients, chest CT manifestations were diverse, mainly presenting as fibrous cord‑like lesions, lymph node enlargement, and sporadic nodules. The incidences of patchy consolidation, air bronchogram, pleural effusion and pleural thickening were higher in anti-IFN-γ autoantibody-positive patients with TM infection than those of controls (P < 0.05). Conclusions Anti-IFN-γ antibody positive patients with TM infection showed a longer diagnostic interval. clinical specimens from which TM was isolated or detected were different between the two groups. The clinical and imaging manifestations of patients with TM infection are characteristic.